Foundation and Motivation of Entrepreneurship in Islam - Holilur Rahman; Ach Subairi; Taufiq Marwina Hakim (Al-Fadilah: Islamic Economics Journal, 2025)
This research aims to determine the foundation and motivation provided by educators in terms of entrepreneurship which will then improve the skills of postgraduate students at Al Amien Prenduan University. This study used qualitative research methods. The author's strategy in research is looking for data sources through books, journals and other scientific works. By multiplying the data. The Prophet Muhammad had a strategy in carrying out entrepreneurial activities in the form of honesty, trustworthiness, self-confidence, spirit, a truly clean business, etiquette, bright prospects, diligent, persistent, independent, never giving up, daring to take risks, and having an egalitarian personality. The application of entrepreneurship to entrepreneurial students cannot be separated from educators who provide entrepreneurial motivation. From the application of entrepreneurship, it will increase the life skills contained in students which include personal skills and social life skills, and along with the implementation of entrepreneurship in students.